Poly(3, 4-ethylenedioxythiophene)/germanium organic–inorganic hybrid thin films: substrate-induced synthesis, enhanced photoelectrochemical and photocatalytic properties. Issue 1 (21st December 2015) - Lu, Peng; Yang, Pei-hui
Abstract : We demonstrate here a facile synthesis of 3D PEDOT nano-flowers/Ge nanoparticles organic–inorganic hybrid films with enhanced photoelectrochemical and photocatalytic performance. Abstract : The unique optoelectronic properties and promising photovoltaic applications of hybrid organic–inorganic composites have driven the exploration of the facile design and fabrication of hybrid materials and corresponding devices. As a step toward both expanding the library of morphological diversity of organic conducting polymers and increasing the species diversity of hybrid organic–inorganic materials that are utilized in optoelectronic devices, we report here the fabrication and enhanced photoelectrochemical properties of a new hybrid organic–inorganic composite consisting of poly(3, 4-ethylenedioxythiophene) (PEDOT) nanoflowers and germanium (Ge) nanoparticles. Aliquot studies revealed that dissolution and deformation of the nanoparticles induced the initial formation of flower-like PEDOT. Furthermore, enhanced photoelectrochemical and photocatalytic properties of hybrid films are realized compared to the bare Ge and PEDOT films, which resulted from the enhancement of the separation of electron–hole pairs photoinduced by the hybrid interface between Ge and PEDOT. The hybrid organic–inorganic composite is promising for cost-effective photovoltaic devices and the design principle provides future opportunities for fabrication of other organic conducting polymers.